2020
DOI: 10.1097/mat.0000000000001202
|View full text |Cite
|
Sign up to set email alerts
|

Central Versus Peripheral Arterial Cannulation for Veno-Arterial Extracorporeal Membrane Oxygenation in Post-Cardiotomy Patients

Abstract: Different arterial cannulation strategies are feasible for veno-arterial extracorporeal membrane oxygenation (VA-ECMO) in postcardiotomy shock. We aimed to analyze potential benefits and safety of different arterial cannulation strategies. We identified 158 patients with postcardiotomy cardiogenic shock requiring VA-ECMO between 01/10 and 01/19. Eighty-eight patients were cannulated via axillary or femoral artery (group P), and 70 centrally via the ascending aorta directly or through an 8 mm vascular graft ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The reports that support a benefit to central cannulation have low sample sizes. 8 , 11 The studies that show improved outcomes with peripheral cannulation include more patients, and include a meta-analysis, but are still retrospective. 9 , 12 , 13 Mariscalco and colleagues 9 published the largest study (apart from meta-analyses) and showed that peripherally cannulated patients had a lower in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reports that support a benefit to central cannulation have low sample sizes. 8 , 11 The studies that show improved outcomes with peripheral cannulation include more patients, and include a meta-analysis, but are still retrospective. 9 , 12 , 13 Mariscalco and colleagues 9 published the largest study (apart from meta-analyses) and showed that peripherally cannulated patients had a lower in-hospital mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The direct cannulation of the ascending aorta allows antegrade flow and avoids concerns with dual circulation (also known as North-South or Harlequin syndrome). 8 , 9 Dual circulation is a phenomenon in which inadequately oxygenated blood from the heart rather than oxygenated blood from the ECMO circuit feeds the head vessels. 10 Another advantage to central cannulation is that if the chest is already open in the operating room central cannulation might be faster than peripheral cannulation.…”
Section: Central Ecmomentioning
confidence: 99%
See 1 more Smart Citation
“…Arterial cannulation can be performed peripherally via femoral or axillary cannulation or centrally via cannulation of the ascending aorta. 37 Visualization of the arterial guidewire within either the descending thoracic aorta or ascending aorta serves as additional confirmation of correct arterial vascular access. This may be especially helpful in cases of profoundly impaired cardiac output and/or oxygenation where identification of the femoral artery can be challenging, especially in the emergent setting.…”
Section: Va-ecmo: Guiding Cannulation and Initiation Of Ecmomentioning
confidence: 99%
“…No consistent data have favored central over peripheral over peripheral strategies. 15,16 Multiple permutations of ECMO cannulation techniques are possible and should be adapted to patients' unique physiology and anatomy. 17 The Impella (Abiomed) is a temporary, percutaneous, transaortic LVAD.…”
Section: Choice Of Mechanical Circulatory Support Strategymentioning
confidence: 99%